A Study of Sleep Habits of the Students of Primary Schools of Rasht City From ‎Parents, Point of View - mehri yuosefgomrokchi; zahra shafi poor; ezat paryad; zahra atarkarruoshan (Journal of Holistic Nursing and Midwifery)
Introduction: Sleep and enough rest are the primary requirements of human, s health and survival ‎and the quality of sleep has a significant role in improving and maintaining health. Sleep habits are ‎effective on the quality and quantity of sleep during childhood.‎